APLIKASI MOTIF ORNAMEN BATIK ABYORHOKOKAI PADA SEPATU SLIP ON APLIKASI MOTIF ORNAMEN BATIK ABYORHOKOKAI PADA SEPATU SLIP ON - Jiyestha, Ni Made Thesa; Nurhidayat, Martiyadi; Muttaqien, Teuku Zulkarnain (eProceedings of Art & Design, 2023)
Slip on shoes are shoe products that are widely used by the general public  in various activities such as hangouts, style or traveling in various kinds of events. In formal and  everyday  events,  some  people  choose  to  use  slip  on  but  with  a  simple  and comfortable style. Shoes that are used  in daily activities or  in certain events, of course, the aesthetic value and beauty of  the  shoes a a  shoe  sill be  considered. So  that when used it will remain stylish and elegant. Slip on shoes as a shoe design that is simple and easy to use are the most popular choices for use in formal events and dailyactivities of the user. The results of the design  of slip on shoes are expected to increase the beauty of the shoes with the combination of ornamental motifs from Abyorhokokai peacock batik and can be used especially by women in daily activities orformal events which of course remain comfortable when used due to the simple form of slip on shoes. Key words: slip on, batik abyorhokokai, ornament.